Soul / [videorecording (Blu-Ray)] - Docter, Pete; Powers, Kemp (Disney/Pixar, 2021)
Joe Gardner is a middle-school band teacher who gets the chance of a lifetime to play at the best jazz club in town. A misstep takes him from New York City to The Great Before, a fantastical place where new souls get their personalities before going to Earth. Determined to return to his life, Joe teams up with a precocious soul, 22, who has never understood the appeal of the human life. As Joe tries to show 22 what's great about life, he may discover the answers to the most important questions.